(A child's first library of learning) Flowers and Trees (Time-Life Books Hong Kong, 2000)
"Flowers and Trees" is a vibrant exploration of the natural world, celebrating the beauty and diversity of plants. The book takes readers on a journey through various landscapes, showcasing a variety of flowers and trees, each with its unique colors, shapes, and roles in the ecosystem. Through engaging illustrations and simple, informative text, children learn about the different species, their habitats, and the importance of plants in our lives. The story fosters a love for nature, encouraging young readers to appreciate and care for the environment while highlighting the vital role that flowers and trees play in sustaining life on Earth.